Urbanization and Non-Communicable Risk Factors in the Capital City of 6 Big Provinces of Iran - AR Mahdavi Hazaveh; K Etemad; SH Yarahmadi; N Azhang (Tehran University of Medical Sciences, 2013)
Background: The prevalence of non-communicable diseases such as hypertension and diabetes including obesity has increased over the past few years in Iran. The increase in these diseases has been associated with increased urbanization and lifestyle changes. The burden of non-communicable diseases (NCD) is increasing in low and middle-income countries. The aim of this report is to address the threat of NCDs in the capital city of 6 big provinces of Iran.Methods: A community based cross sectional study was carried out between March 2010 to January 2011 in 6 provinces' capital cities (Isfahan, Karaj, Mashad, Shiraz, Tabriz, and Tehran). Participants were men and women of 30 years and older who had been screened through the National Diabetes Prevention and Control Program. BMI, blood pressure, fasting blood glucose and lipids were measured.Results: 439406 cases (60% female & 40% male) were studied. The prevalence of pre-diabetes (13%), diabetes (13%), hypercholesterolemia (14%), hypertension (11%), overweight (27%) and obesity (20%) was higher than expected. Only 35% of participants were healthy.Conclusion: This study reveals a high prevalence of NCDs in urban living population in those capital cities. It also shows that increasing urbanization may be an important threat to public health regarding NCDs especially in developing countries. It is crucial to implement a comprehensive NCD program (across the life time) in the health system with a strong collaboration with all stakeholders (governmental and non-governmental sector, academic, research centers and scientific associations) in the community (Multisectoral Approaches).